Quantitative dynamics of PCB transfer from mother to pup during lactation in UK grey seals Halichoerus grypus - Debier, C; Pomeroy, P P; Dupont, C; Joiris, C; Comblin, V; Le Boulenge, E; Larondelle, Y; Thome, J P (2003)
PCB contamination was measured in the milk and serum of grey seal Halichoerus grypus mothers and in the serum of their pups sampled from 2 to 5 times between parturition and weaning on the Isle of May, Scotland, in 1998 and 2000. Blubber biopsies were also taken from the lactating females at early and late lactation in 2000. Concentrations of PCBs in milk stayed constant during the first part of lactation (0.31 +/- 0.17 mug g milk(-1)) and then increased at late lactation (0.67 +/- 0.42 mug g milk(-1)). Curiously, it did not follow the changes of milk lipid content, which increased at early lactation and then stayed constant until the end of the nursing period. As a result, even when expressed per unit of milk lipids, PCBs underwent a rise at the end of lactation. The changes in milk PCBs were accompanied by similar dynamics in maternal serum as well as in pup serum. Increased concentrations of PCBs at late lactation in serum and milk may be explained in part by the changes observed in maternal blubber. PCB levels increased significantly between early and late lactation in inner blubber, suggesting that PCBs are less easily mobilised from blubber than lipids. At late lactation, the retention capacity of the reduced blubber layer for PCBs might have reached its maximum. The mobilization of less polar lipids from blubber might also occur at this stage. In both cases, this could result in a higher mobilization of PCBs at this time. While inner blubber was significantly less concentrated than outer blubber at early lactation (1.26 +/- 0.72 mug g lipids(-1) in inner blubber vs 3.16 +/- 1.34 mug g lipids(-1) in outer blubber), these variations disappeared at late lactation (3.24 +/- 2.60 mug g lipids(-1) in inner blubber vs 3.59 +/- 1.46 mug g(-1) lipids in outer blubber). Newborn pups already had significantly higher serum levels of PCBs than their mothers, revealing an important placental transfer (11.9 +/- 7.0 ng ml serum(-1) in pups vs 6.7 +/- 3.5 ng ml serum(-1) in mothers). These differences were even greater in ...